Chemerin Is Associated with Metabolic Syndrome Phenotypes in a Mexican-American Population - Bozaoglu, Kiymet; Segal, David; Shields, Katherine A.; Cummings, Nik; Curran, Joanne E.; Comuzzie, Anthony G.; Mahaney, Michael C.; Rainwater, David L.; VandeBerg, John L.; MacCluer, Jean W.; Collier, Greg; Blangero, John; et al. (The journal of clinical endocrinology and metabolism, 2009)
Context: Chemerin is a novel adipokine previously associated with metabolic syndrome phenotypes in a small sample of subjects from Mauritius. Objective: The aim of the study was to determine whether plasma chemerin levels were associated with metabolic syndrome phenotypes in a larger sample from a second, unrelated human population. Design, Setting, Patients, and Intervention: Plasma samples were obtained from the San Antonio Family Heart Study (SAFHS), a large family-based genetic epidemiological study including 1431 Mexican-American individuals. Individuals were randomly sampled without regard to phenotype or disease status. This sample is well-characterized for a variety of phenotypes related to the metabolic syndrome. Main Outcomes: Plasma chemerin levels were measured by sandwich ELISA. Linear regression and correlation analyses were used to determine associations between plasma chemerin levels and metabolic syndrome phenotypes. Results: Circulating chemerin levels were significantly higher in nondiabetic subjects with body mass index (BMI) greater than 30 kg/m2 compared with those with a BMI below 25 kg/m2 (P < 0.0001). Plasma chemerin levels were significantly associated with metabolic syndrome-related parameters, including BMI (P < 0.0001), fasting serum insulin (P < 0.0001), triglycerides (P < 0.0001), and high-density lipoprotein cholesterol (P = 0.00014), independent of age and sex in nondiabetic subjects. Conclusion: Circulating chemerin levels were associated with metabolic syndrome phenotypes in a second, unrelated human population. This replicated result using a large human sample suggests that chemerin may be involved in the development of the metabolic syndrome.